2018
DOI: 10.5535/arm.2018.42.1.137
|View full text |Cite
|
Sign up to set email alerts
|

Change of Femoral Anteversion Angle in Children With Intoeing Gait Measured by Three-Dimensional Computed Tomography Reconstruction: One-Year Follow-Up Study

Abstract: ObjectiveTo evaluate femoral anteversion angle (FAA) change in children with intoeing gait depending on age, gender, and initial FAA using three-dimensional computed tomography (3D-CT).MethodsThe 3D-CT data acquired between 2006 and 2016 were retrospectively reviewed. Children 4 to 10 years of age with symptomatic intoeing gait with follow-up interval of at least 1 year without active treatment were enrolled. Subjects were divided into three groups based on age: group 1 (≥4 and <6 years), group 2 (≥6 and <8 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…However, the details remain to be clarified. The anteversion angle of the femoral neck is large in infancy and childhood, and decreases with growth, as reported for the femoral neck shaft angle [6]. A previous study found no reduction in this angle in many patients with DDH [7], but whether the future development of OA depends on this angle in DDH-free patients remains unclear [8].…”
Section: Introductionmentioning
confidence: 80%
“…However, the details remain to be clarified. The anteversion angle of the femoral neck is large in infancy and childhood, and decreases with growth, as reported for the femoral neck shaft angle [6]. A previous study found no reduction in this angle in many patients with DDH [7], but whether the future development of OA depends on this angle in DDH-free patients remains unclear [8].…”
Section: Introductionmentioning
confidence: 80%
“…Kong et al ., in their study of children aged 4–6 years with recently diagnosed intoeing gait, performed 3D CT at the time of diagnosis, and reported that a decrease in the FAA was observed for 18 months ( 10 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Management of these patients should be carried out on an individual basis. According to the current literature, femoral anteversion decreases until 8 years of age [14]. Fabry et al .…”
Section: Discussionmentioning
confidence: 99%